The promise : President Obama, year one - Alter, Jonathan. (Simon & Schuster, 2010)
Jonathan Alter, one of the country's most respected journalists and historians, uses his unique access to the White House to produce the first inside look at Obama's difficult debut. In Alter's telling, the real Obama is an authentic, demanding, unsentimental, and sometimes overconfident leader.